Cable Force Measurement of Cable-Stayed Bridge Based on Microwave Radar Test Technology - Gongjian Che; Ruixin Jia; Kaiquan Liu; Shangqing Zhu; Jianxin Hu (Advances in Civil Engineering)
In recent years, the safety of cables of cable-stayed bridges has attracted extensive attention, and the rise of radar technology has provided new possibilities for the performance testing of cable-stayed bridges. In this regard, this paper introduces the principle of microwave radar measurement technology and uses the microwave cable force measuring instrument to perform noncontact microwave radar cable force measurement on a total of 72 stay cables in Shifeng Bridge and San-Jiadian Bridge compared with the measurement results of the cloud smart collector. The results show that the fundamental frequency deviation rate of 71 cables is within 3%, and the cable force deviation rate of 67 cables is within 5%. This shows that the microwave radar cable force measurement method has a high degree of reliability and accuracy; meanwhile, it is also found that the forces on the left and right sides of the two bridges are in a symmetrical state, and the structure is in good condition; the signal characteristics are obvious, and the simultaneous measurement of multiple cables can be realized, and it is not limited by weather, site, and the length of the stay cable and has strong practical value.